KEBIJAKAN PEMERIKSAAN DIREKTORAT JENDERAL PAJAK SEBAGAI SARANA PENGUJIAN SISTEM PEMUNGUTAN PAJAK SELF ASSESSMENT - Deddy Arif Setiawan (Media Riset Akuntansi, Auditing & Informasi, 2011)
Taxation assessment system which was been used Indonesian, is self assessment system. Taxpayers do to calculate and pay income tax, and to submit a Periodic Tax Return and an Annual Tax Return. Every Taxpayer shall be obliged to complete Tax Return correctly, completely, and clearly. That obligation was been tested by tax audit.Audit is a series of activities to collect and process data, information and or evidence conducted in an objective and professional manner based on an auditing standard in order to assess tax compliance and other objectives for enforcement of provisions of the tax laws. Director General of Taxes has the authority to conduct an audit to test complience of the Taxpayer and for other purposes in respect to the implementation of the tax laws.